2016
DOI: 10.3390/e18090321
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Distortions in the FeCoNiCrMn High Entropy Alloy Studied by Theory and Experiment

Abstract: Lattice distortions constitute one of the main features characterizing high entropy alloys. Local lattice distortions have, however, only rarely been investigated in these multi-component alloys. We, therefore, employ a combined theoretical electronic structure and experimental approach to study the atomistic distortions in the FeCoNiCrMn high entropy (Cantor) alloy by means of density-functional theory and extended X-ray absorption fine structure spectroscopy. Particular attention is paid to element-resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 178 publications
(87 citation statements)
references
References 45 publications
10
76
0
1
Order By: Relevance
“…31,32 Solid solution hardening-effect of individual elements The CoCrFeMnNi HEA is a highly alloyed material, and a severe lattice distortion and high solid solution hardening effect have been expected. 14,33 However, the effect of individual elements on the strength, which is highly necessary for an alloy design of HEAs with an improved strength, is insufficiently known. One study presented a systematic report for the effect of individual elements on the strength of this alloy: the yield strength (YS) of the CoCrFeNi, CoCrMnNi, CoFeMnNi HEA as well as the CoCrFeMnNi HEA.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Solid solution hardening-effect of individual elements The CoCrFeMnNi HEA is a highly alloyed material, and a severe lattice distortion and high solid solution hardening effect have been expected. 14,33 However, the effect of individual elements on the strength, which is highly necessary for an alloy design of HEAs with an improved strength, is insufficiently known. One study presented a systematic report for the effect of individual elements on the strength of this alloy: the yield strength (YS) of the CoCrFeNi, CoCrMnNi, CoFeMnNi HEA as well as the CoCrFeMnNi HEA.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, recent studies, both theoretical and experimental ones, do not support the original idea of 'severe' lattice distortions [16,17,18]. Combined theoretical and experimental study [16] revealed that the mean strains in CoCrFeMnNi are relatively small, below 1%, but their fluctuations are significant. The hypothesis about the 'cocktail' effect is probably most vaguely defined and difficult to test it rigorously [13].…”
Section: Introductionmentioning
confidence: 80%
“…Tsai et al [19] estimated two different values of the interdiffusion coefficients, as shown in Figure 3b. In response [54] to the comment [53], they defended their approach of estimating two different interdiffusion To instigate further on this issue, two sentences from the manuscript by Tsai et al [16] are highlighted:…”
Section: 4mentioning
confidence: 99%
“…As we are interested in the impact of internal atomic relaxations, the total energy above is split into the contributions arising from the static bcc lattice, E σ static , and the energy contribution due to internal relaxations, denoted as ∆E σ relax . Indeed, lattice distortions constitute one of the main features in HEAs [7][8][9], and have been investigated, for example, for the FeCoNiCrMn (Cantor) HEA recently [25]. For binary alloys, the importance of relaxation energies to phase stability computations have been recognized some time ago (e.g., [26][27][28]).…”
Section: Resultsmentioning
confidence: 99%